Increasing student engagement and retention using online learning activities wikis, blogs and webquests - Charles Wankel; Patrick Blessinger (Bingley, U.K. : Emerald, 2012)
Increasing Student Engagement and Retention using Online Learning Activities: Wikis, Blogs and WebQuests uses case studies, surveys, and literature reviews to critically examine how these technologies are being used to improve writing and publishing skills, student subject awareness, and literacy create engaging communities of practice, and as experiential learning tools. Chapters include ones on the design for a robust use of wikis, using blogs to enhance student engagement by creating a community of practice around a course, integrating blogs across a range of college level courses, publishing activist biographies on Wikipedia, using blogs to increase off-campus student engagement, using video and wiki technology to engage learners in large international cohorts, using wikis as an experiential learning tool, consuming and constructing knowledge through WebQuests, and rethinking WebQuests in second language teacher education. This volume will also discuss frameworks for deploying and assessing the effectiveness of these technologies.
New directions in higher education : an introduction to using wikis, blogs, and webquests / Patrick Blessinger, Charles Wankel -- Cooperating or collaborating : design considerations of employing wikis to engage college-level students / Jane Strickland, Ying Xie -- Blogging all over the world : can blogs enhance student engagement by creating a community of practice around a course? / Tony Reeves, Phil Gomm -- Blogging is addictive! : a qualitative case study on the integration of blogs across a range of college level courses / Natascha Radclyffe-Thomas -- Writing radical lives : undergraduates publishing activist biographies on Wikipedia / Linda S. Watts -- Blogging clinical placement : harnessing technologies to increase off-campus engagement with healthcare learners / Stephanie Mckendry, Vic Boyd -- Using video and wiki technology to increase student engagement with learning in large international cohorts in UK higher education / Elisabeth Dunne, Jenny Wren, Alex Janes -- Using the wiki as an experiential learning tool to engage students in undergraduate and graduate university courses / Michael J.D. Sutton, Afsaneh Hazeri -- Academic literacies and blog writing in university classrooms / Cecile M. Badenhorst -- Consuming and constructing knowledge through WebQuests / Hope J. Hartman -- Rethinking WebQuests in second language teacher education : the case of one Colombian university / Raúl Alberto Mora ... [et al.].
Includes index.
Print version record
Keywords: Education -- Computers & Technology; Education -- Distance Education & Learning; Teachers' classroom resources & material; Educational: IT & computing, ICT; Internet in higher education; Education, Higher -- Simulation methods